Profiles of Resilience, Distress, and Posttraumatic Growth in Parents of Children with Cancer and the Relation to Subsequent Parenting and Family Functioning. (20th January 2023) - Howard Sharp, Katianne M; Tillery Webster, Rachel; Cook, Jessica; Okado, Yuko; Long, Alanna; Phipps, Sean
Abstract: Objective: The aim of this study was to identify patterns of distress and growth in parents of children with cancer and examine associations with subsequent parenting, parent–child relationship, and family environment. Methods: Participants included children with cancer history (8–17 years) stratified by time since diagnosis and their parent. At enrollment, parents ( n = 254) reported depression and anxiety, and post-traumatic stress symptoms, posttraumatic growth (PTG), and benefit finding in relation to their child's cancer. Three years later, children ( n = 214) reported parenting behavior, parent reactions to their distress, and family environment. Parents reported their reaction to children's distress and qualities of the parent–child relationship. Results: Latent profile analysis empirically identified 3 cross-sectional profiles using baseline data: "Resilience, High Growth" (50%), characterized by the lowest distress and the highest PTG/benefit finding; "Moderate Distress with Growth" (33%), characterized by relatively high levels of all indicators; and "Resilience, Low Growth" (17%), characterized by relatively low distress with low PTG/benefit finding. Membership in profiles was associated with parent gender; parents' stressful life events; socioeconomic status; and child diagnosis, on versus off treatment status, and treatment intensity. Parent membership in the Moderate Distress with Growth profile was generally linked with poorer parenting behavior, parent–child relationship quality, and family functioning. Conclusion: The majority of parents exhibited resilience and growth. However, a subset of parents displaying moderate distress may be at risk for subsequent parenting and family functioning challenges. Findings further highlight the importance of screening for even moderate parent distress and the possible impact of parent psychosocial interventions indirectly on parenting and family functioning.